Neck circumference in children and adolescents –an emerging tool for screening central obesity - Malini, M; Kalpana, S; Lakshmi, S (Indian Journal of Child Health, 2025)
Objectives: The aim of the study was to validate the utility of neck circumference (NC) as an anthropometric measure of the central obesity and its correlation with body mass index (BMI) and waist circumference (WC). The aim of the study was to determine age and gender specific NC cutoffs for screening central obesity. Materials and Methods: This descriptive study was conducted in 1139 children and adolescents aged 6–17 years. NC, WC, and BMI were measured. To define overweight and obesity in children, the 23rd and 27th adult equivalent lines for BMI as presented in the revised Indian Academy of Pediatrics growth charts were used. Results: Overweight and obese children had significantly higher NC than those with normal BMI (p